CRYPTOCURRENCY: DO KNOWLEDGE AND EMOTION IMPACT INVESTMENT INTENTION? (STUDY ON YOUNG ADULTS IN MANADO) - Raphael Excelsio Fredrich Paat; Paulus Kindangen; Lawren Julio Rumokoy (Universitas Sam Ratulangi, 2023)
Over the past few years, especially during the Covid-19 pandemic where many industries have turned to market digitization, transaction activities in crypto investment have increased quite significantly. The purpose of this research is to investigate how Investment Knowledge and Fear of Missing Out influence young adult's Investment Intention in cryptocurrency assets. This research was conducted with a quantitative approach by analyzing the Linear Regression equation using the Ordinary Least Squares (OLS) technique to get the most relevant results. The data source used is primary, where data is collected through a questionnaire with a total of 125 respondents among young adults in the city of Manado. Data processing uses several software, such as Stata 16/MP and Microsoft Excel 2013.The results of this study indicate that there is a positive influence related to Investment Knowledge and Fear of Missing Out on Investment Intention. Knowledge of investment can increase the intention of young adults to invest in cryptocurrency assets. Meanwhile, fear of missing out also has the ability to trigger investment intention among young adults in cryptocurrency assets. This study recommend that the developers should be able to provide in-depth information related to crypto, also information about systematics and instruments in order to attract more investors and strengthen the market of digital investment. Keywords: Cryptocurrency, investment behavior, FOMO, digital investment, fintech